DAYA SAING EKSPOR PALA INDONESIA DI PASAR INTERNASIONAL - Asrol Asrol; Heriyanto Heriyanto (DINAMIKA PERTANIAN, 2017)
Indonesia is one of the largest producing and exporting countries for nutmeg commodities in the world market. Indonesia as a nutmeg exporting country is a country that imports nutmeg products. Nutmeg is one of Indonesia's leading spice export commodities on the world market. Based on the description in general, this study aims to analyze the competitiveness of Indonesian nutmeg in the world market. Specifically, this study aims to analyze the export position of nutmeg and the competitiveness of Indonesian nutmeg in the international market. The power used in this study is secondary time series data from 2007-2016. To answer the research objectives, it was analyzed using the Trade Specialization Index (ISP), Revealed Comparative Advantage (RCA) and Constant Market Share (CMS). Based on the results of the study indicate that for the position of Indonesian nutmeg exports on the world market, the average value of Indonesian ISPs on the world market from 2007-2016 was 0.988. This value indicates that the position or stage of Indonesian nutmeg export is at the maturity stage with an indicator value (0.81-1.00). Furthermore, the competitiveness of the results of the average Indonesian nutmeg RCA value on the international market which is calculated from 2007-2016 reached 19,554 because the value of Indonesian nutmeg RCA is greater than one, so Indonesia has a strong competitiveness in the export of nutmeg in the world and tends to be a country exporter rather than importer. For the CMS value of Indonesian nutmegs in the last five years period is negative on the standard growth, composition effects, and market distribution effects but the positive value on the effect of competitiveness.